2021
DOI: 10.1002/ppul.25756
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter retrospective study of clinical features, laboratory characteristics, and outcomes of 166 hospitalized children with coronavirus disease 2019 (COVID‐19): A preliminary report from Iranian Network for Research in Viral Diseases (INRVD)

Abstract: Background The objectives of this study were to analyze the clinical features and laboratory profiles and risk factors associated with critical illness of children with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Methods One hundred and sixty‐six coronavirus disease 2019 (COVID‐19) Iranian pediatric patients were recruited through a collaborative research network between March and May 2020. Demographics, clinical, laboratory, and radiological results were obtained from patient files. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
3
4
0
Order By: Relevance
“…Abnormal findings were found at a rate of 33-54% in studies examining the results of chest radiography [8, 16]. In our study, this rate was found to be 14%.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Abnormal findings were found at a rate of 33-54% in studies examining the results of chest radiography [8, 16]. In our study, this rate was found to be 14%.…”
Section: Discussionsupporting
confidence: 61%
“…However, it is noteworthy that it is significantly higher in hospitalized patients. Abnormal findings were found at a rate of 33-54% in studies examining the results of chest radiography [8,16]. In our study, this rate was found to be 14%.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies have reported rates of CXR abnormalities of 33 to 54%, 8,18 compared with 15% in our study. In a previous Turkish pediatric study, Böncüoğlu et al found that abnormal CT findings correlated with elevated CRP levels.…”
Section: Discussionsupporting
confidence: 53%
“…8,9,[11][12][13][14][15] As in our study, the most common symptoms are usually reported to be fever and cough. 8,9,[11][12][13][14][15][16][17][18] However, in a UK study of 1,734 children, the most common symptoms were headache (62%) and fatigue (55%). 19 SARS-CoV-2 infections in children have different paths and are less severe than in adults in terms of clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%